UPAYA PENYELENGGARAAN KUALITAS PELAYANAN PADA PT. XYZ DI KABUPATEN GRESIK - Riris Dia Mariati; Sukaris Sukaris (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
One important aspect in increasing competitiveness is improving service quality. Customer expectations are constantly changing, thus requiring adjustments to the quality of the services produced. Customers will evaluate a company's service by comparing it to other similar businesses and also comparing the service they receive to what they expected. no exception the company PT. XYZ, a company engaged in the food sector, is a company that continues to be committed to maintaining its services so that customers do not switch to other companies. This research is a research with a qualitative approach with the aim of understanding human or social phenomena by creating a comprehensive picture that can be presented in words. Data collection is carried out by means of triagulation (combined), used to investigate the condition of the object. Based on the results of the study conducted, it shows that service quality has the potential to create customer satisfaction and customer loyalty, so improving service is an important strategy in maintaining close customer relationships. Any company that provides good customer service has a better chance of success and growth than a company that is not as interested in customer service. Apart from the quality of service, companies need input or comments through complaints so that companies can self-introspect regarding weaknesses and deficiencies in providing excellent service to customers. Keywords: Service Quality, Satisfaction, Loyalty, Complaints.